The Role of Environmental Law in Enhancing Corporate Social Responsibility for Environmental Protection - Wahyudi, Rikes; Rahmatiar, Yuniar; Abbas, Muhamad (Universitas Internasional Batam, 2025)
Environmental law plays an important role as a regulatory instrument that strengthens the implementation of CSR. By accentuating CSR, environmental rules serve to ensure that corporations do not merely prioritize profit, but are also accountable for the ecological consequences of their activities. This research utilizes the normative jurisprudence method. This approach technique was chosen because the primary data used is secondary data, namely data collected through literature review and supporting data such as interviews and sources related to information on the role of Environmental Law in CSR accessntuation. The effectiveness of CSR, although guided by regulation, depends heavily on the integration of social and environmental responsibility in the company's business. The Karawang Regency Government and Tegal Sawah Village play a crucial role in ensuring that environmental CSR is effective. Weak oversight will damage the environment and hinder sustainability. The government can create positive impacts for the environment and Tegal Sawah Village community through better supervision, community engagement and collaboration with companies.